Internalisasi Nilai-Nilai Syukur: Upaya Penguatan Spiritualitas Civitas Akademika Universitas BSI Margonda Depok - Endang Madali (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Safari Ramadhan is a religious activity conducted by Universitas Bina Sarana Informatika (UBSI) Margonda Depok as part of its community service program aimed at strengthening spiritual values within the academic environment. This activity seeks to internalize the value of gratitude (syukur) among university leaders and staff, under the theme “The Beauty of Fasting with Knowledge and Righteous Deeds.” The program was delivered through interactive lectures and reflective discussions led by a religious scholar and academician. The method employed included educational and participatory approaches that encouraged active engagement. The results indicate a significant increase in participants' spiritual awareness and work motivation. Participants expressed a deeper understanding of gratitude as a foundational value for personal development and professional responsibility. Furthermore, the activity fostered a stronger sense of togetherness and harmony within the university. The Safari Ramadhan program proved to be an effective strategy for character building and spiritual reinforcement in the higher education environment